2014
DOI: 10.1080/08946566.2013.792104
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Evaluation of a Multidisciplinary Social Work–Lawyer Elder Mistreatment Intervention Model

Abstract: This study introduces a conceptually based, systematic evaluation process employing multivariate techniques to evaluate a multidisciplinary social work-lawyer intervention model (JASA-LEAP). Logistic regression analyses were used with a random sample of case records (n = 250) from three intervention sites. Client retention, program fidelity, and exposure to multidisciplinary services were significantly related to reduction in mistreatment risk at case closure. Female gender, married status, and living with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The LEAP program had success in assisting victims take action against their abusers. In another study of LEAP, Rizzo et al (2013) developed their study design grounded in a strong conceptually-based, systematic evaluation process and multivariate techniques. Logistic regression analyses were used with a random sample of case records from three intervention sites.…”
Section: Multidisciplinary and Interdisciplinary Teamsmentioning
confidence: 99%
“…The LEAP program had success in assisting victims take action against their abusers. In another study of LEAP, Rizzo et al (2013) developed their study design grounded in a strong conceptually-based, systematic evaluation process and multivariate techniques. Logistic regression analyses were used with a random sample of case records from three intervention sites.…”
Section: Multidisciplinary and Interdisciplinary Teamsmentioning
confidence: 99%
“…The VHA is the largest healthcare system in the United States, presenting immense opportunity for developing, testing, and disseminating innovative programs for elder abuse interventions. In many settings, successful elder abuse programs have been multidisciplinary . The VHA is an ideal environment for integrated, multidisciplinary approaches.…”
Section: Call To Action: Expand Knowledge and Improve Care Of Veteranmentioning
confidence: 99%
“…Similar to APS, however, community-based elder mistreatment programs seek to develop a service plan and intervene on substantiated elder mistreatment cases towards the overall goal of revictimization risk alleviation (Burnes, 2016). Research based on case review analysis provides preliminary support for community-based elder mistreatment programs in alleviating revictimization risk by empowering victims to take action to stop the cycle or remove themselves from the abusive situation (Cripps, 2001; Lithwick, Beaulieu, Gravel, & Straka, 2000; Rizzo, Burnes, & Chalfy, 2015). Cripps used a rights focused advocacy model, which enabled victims to stop abuse in 50% of the cases and take action in 34% of the situations, while Lithwick et al suggested a harm-reduction model to guide interventions.…”
Section: State-of-the-science Related To Abuse Prevention: Applicatiomentioning
confidence: 99%
“…Evidence suggests that programs integrating a multidisciplinary approach such as incorporating social services and criminal justice systems have merit because they can reduce revictimization risks (Brownell & Wolden, 2002; Rizzo et al, 2015). For example, Rizzo et al evaluated a social worker-lawyer intervention model using a multivariate approach, and showed that client retention, program fidelity, and exposure to MDT were related to reduced mistreatment risk at case closure.…”
Section: State-of-the-science Related To Abuse Prevention: Applicatiomentioning
confidence: 99%
See 1 more Smart Citation